OF THE SOCIO-DEMOGRAPHIC GROUP OF WOMEN AND CHILDREN CHARACTERISTICS - Suyumova Markhabo; M. Abdurahmonova (Western European Studies, 2024)
This in the article, social demographic groups about information and social demographic of the group big features about information given their Women and children features about wide data given passed
Keywords: demography; protection; importance